Inhibition of IRAK 1/4 alleviates colitis by inhibiting TLR4/ NF-κB pathway and protecting the intestinal barrier - Bo Yan; Xiangjie Li; Linxiang Zhou; Yuqing Qiao; Jing Wu; Lanlan Zha; Peilu Liu; Shuai Peng; Baixin Wu; Xiaoyun Yu; Lei Shen (Biomolecules & Biomedicine, 2022)
Interleukin-1 receptor-associated kinase 1/4 (IRAK1/4) is the main kinase of the Toll-like receptor (TLR)-mediated pathway, considered a new target for treating inflammatory diseases. Studies showed a significant correlation between TLRs and inflammatory responses in ulcerative colitis (UC). Therefore, in this study, after inducing experimental colitis in mice with 3% dextran sulfate sodium (DSS), different concentrations of IRAK1/4 inhibitors were administered intraperitoneally. Then, the disease activity index was assessed, including the degree of pathological damage, by HE staining. Subsequently, while western blotting detected the TLR4/NF-κB pathway and intestinal barrier protein expression (Zonula-1, Occludin, Claudin-1, JAM-A), real-time polymerase chain reaction (RT-PCR) detected the mRNA expression levels of IRAK1/4 and mucin1/2. Furthermore, the expression levels of Zonula-1 and occludin were detected by immunofluorescence, including the plasma FITC-dextran 4000 concentration, to evaluate intestinal barrier permeability. However, ELISA measured the expression of inflammatory factors to reflect intestinal inflammation in mice. Investigations showed that the IRAK 1/4 inhibitor significantly reduced clinical symptoms and pathological DSS-induced colitis damage in mice and then inhibited the cytoplasmic and nuclear translocation of NF-κB p65, including the phosphorylation of IκBα and reduction in downstream inflammatory factor production. Therefore, we established that the IRAK1/4 inhibitor effectively improves colitis induced by DSS, partly by inhibiting the TLR4/NF-κB pathway, reducing inflammation, and maintaining the integrity of the colonic barrier.